The role of income support systems as income stabilizers in times of crisis - Mathias Dolls; Max Lay (CESifo GmbH, 2023)
This Policy Brief examines how minimum income support (MIS) schemes contribute to the stabilization of disposable incomes in times of crisis in Europe. MIS systems act as a "safety net of last resort" in many European welfare states, but to varying degrees. The results from the simulation of stylized unemployment shocks hitting labor markets suggest that the tax-transfer system overall contributes to income stabilization in periods of crises. However, the MIS schemes' individual contribution is relatively small, especially as set against the unemployment insurance system.
Keywords: 330; Öffentliche Sozialleistungen; Arbeitslosenversicherung; Automatischer Stabilisator; Konjunktur; Schock; Simulation; Vergleich; Sozialstaat; Europa